In Vitro Study of Interactions of Carboxamide Derivatives of Amino Acid with BSA: Ultrasonic Interferometer - Thakare, Shrikant Bandupant; Tekade, Pradip Vitthalrao; Pisuddes, Ajay Madhukarrao (Orbital: The Electronic Journal of Chemistry, 2018)
In this paper we account the interaction of the Carboxamide derivatives of amino acid viz 2-[2-(cyclohexycarbamoyl) benzoyl] amino propanoic acid (2CMPA), 2-Benzamido acetic acid 2-cyclohexyl carboxamide (2BA2C), 2-[2-(cyclohexylcarbamoyl) benzoyl] amino-3-methylbutanoic acid (2CA3MBA), 2-benzamido-4-methylpentanoic acid-2-cyclohexyl carboxamide (2-BMCA) and 2-[2-(cyclohexycarbamoyl) benzoyl] amino-4-(methylsulfanyl) butanoic acid (2CA4MBA) with protein Bovine serum albumin (BSA) using ultrasonic interferometer technique. Ultrasonic velocity for complex solution of different compounds of carboxamide derivatives of amino acid with BSA has been measured at their different composition using ultrasonic interferometer. Difference in the ultrasonic velocity at different compositions of complex is measure of binding of the compounds with BSA. Binding effect at various pH viz. 3, 4 and 5 shows that compounds bound to the BSA more significantly at acidic pH and association constant decreases with increase in pH value. Scatchard analysis gives the values of association constants (Kf) for all the compounds at pH 3, 4 and 5 respectively. DOI: http://dx.doi.org/10.17807/orbital.v10i5.1161